Complex processing geophysical survey and selection of methods for detailing the geological structure of mega-reservoirs (Hayan block, of the Palmyride fold belt) - V. L. Schuster; O. V. Tyukavkina; I. Kartal (Известия высших учебных заведений: Геология и разведка, 2024)
Background. An analysis was conducted out to establish the boundaries of the Kurrachi-Dolomite formation reservoir (Jihar field, Hayan block, Palmyra fold belt). In the process of research, data from geophysical surveys of wells were used and statistical processing of the obtained data was carried out. Currently, due to the difficult situation in Syria, scientific research in this area is extremely limited.Aim. To conduct a combined processing of geophysical well data (GWD), including by using a correlation matrix, and to assess the applicability the results obtained as an express method for interpreting geophysical data and identifying the boundaries of the Kurrachine-Dolomite formation within the Hayan block and adjacent areas.Materials and methods. The well data for the empirical study was provided by the Syrian Petroleum Company. Correlation matrices were obtained between the following logging data: CAL, AC, GR, RD, RS, RHOB, and PE. This allowed a good correlation to be determined between their numerical values and the results of core studies, which were carried out to establish lithological characteristics and reservoir properties of the area under study (northwestern part of the Hayan block).Results. The processed materials made it possible to select the most effective GWD combination for identifying the boundaries and fringe zones of sediments in the Kurrachine-Dolomite formation, considered as a mega reservoir, and to identify priority development objects similar in geological structure and reservoir properties.Conclusion. The proposed method for processing field geophysical materials (construction of correlation matrices and statistical processing of geological and field data) can be used in selecting an optimal combination of GWD for establishing the reservoir boundaries of the Kurrachine-Dolomite formation, quantifying the reservoir properties, and increasing the efficiency of the Jihar field development (mega reservoir of the Hayan block).